Implementation of Global Diversity Dimension in Education of Pancasila Student Profile Strengthening Project at Kemala Bhayangkari Kindergarten Palembang - Marlina, Leny; Afifah Nabila Sari; Dewi, Kurnia; Febrianita Putri, Yecha (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan UIN Raden Fatah, 2024)
This study aims to describe the implementation of the dimensions of global diversity in the education project of strengthening the profile of Pancasila students at Kemala Bhayangkari 1 Palembang Kindergarten and analyze what are the supporting and inhibiting factors in the implementation of the project at the school. The research method used is phenomenological qualitative method. The data collection process is done directly through interviews, observation, and documentation. To ensure the trustworthiness of the data, information obtained from informants is then validated using triangulation. The analysis techniques used in this research are data collection, data reduction, data presentation, and conclusion. Based on the results of the study, it shows that the implementation of the dimensions of global diversity in the education project of strengthening the profile of Pancasila students at Kemala Bhayangkari 1 Palembang Kindergarten has been carried out in accordance with the learning objectives in the teaching module that has been designed and students have a better sense of diversity. The implementation of this project is supported by very adequate school facilities and infrastructure as well as teachers who are very instrumental in implementing the project where teachers design modules and carry out each stage of project activities in accordance with their focus, namely the dimensions of global diversity.